Feasibility of a social media-based weight loss intervention designed for low-SES adults. Issue 4 (27th July 2020) - Cavallo, David N; Martinez, Rogelio; Webb Hooper, Monica; Flocke, Susan
Abstract: Low-socioeconomic status (SES) individuals have higher rates of obesity. Social media platforms are used frequently by low-SES individuals and facilitate important weight loss program components including social support. Very few social media-based weight loss interventions, however, have enrolled or been tailored to low-SES participants. The purpose of this article is to examine the feasibility of a social media-based weight loss intervention among low-SES adults. We conducted a one-group pretest post-test pilot intervention study with two groups (group 1, n = 39, group 2, n = 16) of low-SES overweight/obese adults who were enrolled in a 12-week social media-based weight loss intervention including self-monitoring via Fitbits and participation in a private Facebook group. A moderator provided educational content and encouraged social support via Facebook. Descriptive statistics were used to assess intervention acceptability and engagement. Exploratory analyses were conducted to examine changes in study outcomes and engagement patterns. The study had good retention (86%). Among 55 total participants enrolled, there were 9, 175 participant interactions within the Facebook group. Among completers ( n = 47), 96% indicated they would recommend the intervention to a friend. Mean weight loss was 1.07 kg ( SD = 3.96, p = .0498), and participants reported increases in positive dietary social support (mean = 2.47, SD = 5.09, p = .0007). Engagement in this social media-based pilot intervention was high and exceeded results from previous studies using similar formats. Participants evaluated the intervention favorably. Changes in weight loss and several theoretical mediators were in the desired direction. Overall, our results indicate social media groups as a platform for weight loss intervention delivery among low-SES adults are feasible and should be studied in larger randomized trials. Abstract : Adults with low income found a weight loss program that used Facebook valuable, contributed a large amount of content to the Facebook weight loss group, and reported increased social support.